Folic acid supplementation among students - Paulina Piotrowska; Justyna Wójcik; Aleksandra Obuchowska; Alicja Ozga; Żaneta Kimber-Trojnar; Bożena Leszczyńska-Gorzelak (Kazimierz Wielki University, 2019)
Introduction: Pregnancy is a period in which the supply of vitamins, micro- and macroelements is essential for the proper growth of the fetus. One of the most important substances, which is believed to have a considerable influence on the proper fetus growth is folic acid. Folic acid (i.e. vitamin B9) plays a significant role in rapidly dividing cells and lack of this vitamin causes serious fetal defects - for example neural tube anomalies. Supplementation is important not only during pregnancy but also during the period of pregnancy planning. Methods: Students' knowledge regarding the importance of folic acid supplementation was verified using anonymous Internet questionnaire. The obtained results were analyzed using statistical methods and checked on the basis of scientific literature. Results: The percentage of students who supply folic acid is 18,1% and only 9,5% do this regularly. The most common cause of supply is due to the fact that that folate can be found in vitamin kits students usually take. Part of respondents claim that they plan the pregnancy and want the fetus to develop correctly. Other causes of vitamin B9 intake is prevention of arteriosclerosis, vascular system diseases, anemia, lung, esophagus and uterus cancer. Conclusion: Outcomes showed that students are not fully aware of the importance of vitamin B9 during pregnancy and there is a great need to share knowledge about folic acid supplementation among people in procreative age.